Social prescribing outcomes: a mapping review of the evidence from 13 countries to identify key common outcomes - Sonke, Jill; Manhas, Nico; Belden, Cassandra; Morgan-Daniel, Jane; Akram, Seher; Marjani, Stefany; Oduntan, Oluwasanmi; Hammond, Gabrielle; Martinez, Gabriella; Davidson Carroll, Gray; Rodriguez, Alexandra K.; Burch, Shanaé; et al. (Frontiers in Medicine, 2023)
As a means for supporting a range of health and wellbeing goals, social prescribing programs have been implemented around the world. Reflecting a range of contexts, needs, innovation, and programing, a broad array of outcomes has been studied in relation to these programs. As interest in social prescribing grows, more targeted study of key outcomes and in turn evidence synthesis that can inform evidence-based practice, policy, and investment is needed. This mapping review identified, described, and synthesized the broad array of social prescribing outcomes that have been studied in 13 countries and maps the outcomes that have been most commonly studied. From 87 articles included in this review, a total of 347 unique outcomes were identified, including 278 unique patient outcomes and 69 unique system outcomes. The most commonly studied categories of patient outcomes were found to be mental health, lifestyle and behavior, and patient/service user experience. The most commonly studied system outcomes were healthcare/service utilization and financial/economic outcomes. This review highlights the value of heterogeneity and mixed methods approaches in outcomes studies for capturing nuanced experiences and outcomes in this nascent area of practice, while contributing to the advancement of evidence synthesis for social prescribing globally by quantifying and offering insight into the outcomes that have been studied to date. It also lays a foundation for the development of key common outcomes and a Core Outcomes Set for social prescribing. Additionally, it identified key outcomes that, given their relationship to critical health and social issues, warrant both broader and deeper study. and to strengthen community connections" (1). SP programs seek to address social determinants of health or underlying and systemic causes of health issues and inequities, to fill the gap between clinical and non-clinical services, and to broaden the landscape of health promotion to include local community-based resources. It recognizes that individuals have social needs related to health that can be addressed in their community.SP programs have been implemented -at various levels of scale -in at least 17 nations, including the United